2019
DOI: 10.1021/acs.inorgchem.9b00158
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Doped Spherical Hollow-Porous Silicon Local Lattice Expansion toward a High-Performance Lithium-Ion-Battery Anode

Abstract: Silicon (Si) attracts extensive attention as the advanced anode material for lithium (Li)-ion batteries (LIBs) because of its ultrahigh Li storage capacity and suitable voltage plateau. Hollow porous structure and dopant-induced lattice expansion can enhance the cycling stability and transporting kinetics of Li ions. However, it is still difficult to synthesize the Si anode possessing these structures simultaneously by a facile method. Herein, the lightly boron (B)-doped spherical hollow-porous Si (B-HPSi) ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Moreover, the larger pores can also help in promoting better SEI formation and overall structure preservation . The interconnected porous structure also promotes the efficient transport of electrons and lithium ions . The methods for preparing porous silicon mainly include magnesiothermic reduction and acid/alkali etching.…”
Section: Suitable Structural Design Of Silicon Anodementioning
confidence: 99%
“…Moreover, the larger pores can also help in promoting better SEI formation and overall structure preservation . The interconnected porous structure also promotes the efficient transport of electrons and lithium ions . The methods for preparing porous silicon mainly include magnesiothermic reduction and acid/alkali etching.…”
Section: Suitable Structural Design Of Silicon Anodementioning
confidence: 99%
“…The latter Si subgrains are dedicated to the high cycling stability by alleviating the volume change. [101] Unlike B doping (p-type) with higher insertion potential, the P-doped Si has lower Li insertion potential, indicating the smaller thermodynamic driving force for lithiation. [106][107] Sakaguchi et al have investigated the effect of P dopant on reactive behavior and the electrochemical performance of Si electrodes.…”
Section: Si-based Electrodesmentioning
confidence: 99%
“…[117] Furthermore, O vacancies can promote phase transition at the electrode/electrolyte interface by the modification of surface thermodynamics and avoid the structural disintegration on the electrode surface. [118] For instance, intrinsic structural instabilities of MnO with wurtzite Reproduced with permission from Ref., [101] Copyright 2019, American Chemical Society. (b) Schematic diagram and long cycling performance (when coated with carbon and graphene oxide) of porous Si from Fe and B defect etching.…”
Section: Transition Metal Oxides and Derivativesmentioning
confidence: 99%
“…Boron (1s 2 2s 2 2p 1 ), as a graphitization catalyst, can significantly enhance the graphitization of carbon . Boron doping could modify the electronic properties of the graphitic framework, which is beneficial for lithium ion transport behavior . It has been widely confirmed that boron doping can improve the specific capacity and coulombic efficiency of Si‐based composite anode.…”
Section: Boron Dopingmentioning
confidence: 99%